Model of Care for Adolescents and Young Adults with Cancer: The Youth Project in Milan - Magni, Chiara; Veneroni, Laura; Silva, Matteo; Casanova, Michela; Chiaravalli, Stefano; Massimino, Maura; Clerici, Carlo Alfredo; Ferrari, Andrea (Frontiers in Pediatrics, 2016)
Adolescents and young adults (AYA) with cancer form a particular group of patients with unique characteristics, who inhabit a so-called “no man’s land” between pediatric and adult services. In the last ten years, the scientific oncology community has started to pay attention to these patients, implementing dedicated programs. A standardized model of care directed towards patients in this age range has yet to be developed and neither the pediatric nor the adult oncologic systems perfectly fit these patients’ needs. The Youth Project of the Istituto Nazionale Tumori in Milan, dedicated to adolescents and young adults with pediatric-type solid tumors, can be seen as a model of care for AYA patients, with its heterogeneous multidisciplinary staff and close cooperation with adult medical oncologists and surgeons. Further progress in the care of AYA cancer patients is still needed to improve their outcomes.